1975
DOI: 10.1111/j.1439-0507.1975.tb03611.x
|View full text |Cite
|
Sign up to set email alerts
|

Aortitis paracoccidioidomycotica

Abstract: Zusammenfassung Unter 49 autopsierten Paracoccidioides‐Mykosen fanden sich 4 Fälle hämatogen ent‐standener fungischer Aortitis. Nachfolgende Thrombose führte in 3 Fällen zu schweren Zirkulationsstörungen der Beine, in einem zur Nekrose des Darms und der Milz durch Embolien der entsprechenden Arterien. Fungische Absiedelungen innerhalb der Aorten‐wand sind bei Paracoccidioides‐Mykose offenbar nicht so selten, bisher allerdings nur in Venezuela beobachtet. Ihre wahre Natur kann auch autoptisch leicht verkannt we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Although PCM disease is common and endemic in Brazil, there are no recent descriptions of vascular involvement as in the present case. Less than 10 cases have been described in the literature, with the last report dating from 1998 [11][12][13][14][15]. In all reports, the patients were adults, and the diagnosis was delayed or made only at autopsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PCM disease is common and endemic in Brazil, there are no recent descriptions of vascular involvement as in the present case. Less than 10 cases have been described in the literature, with the last report dating from 1998 [11][12][13][14][15]. In all reports, the patients were adults, and the diagnosis was delayed or made only at autopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent review of endemic mycoses showed that PCM is the disease with the least diagnostic tools available [10]. Although PCM is endemic in Brazil, there are few reports of PCM with vascular involvement, the vast majority of which are confused with arteriosclerotic manifestations [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%